Examining trajectories of gender equality in sport for development: A text mining analysis - Javani, Vajiheh; Campillo, Philippe; Caballero, Daniel; Sobry , Claude; Bouchet, Patrick (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The study aimed to identify key themes in gender equality discourse within sport for development (SFD) literature, map their evolution, and assess the influence of sociopolitical contexts on gender equality approaches in SFD. The methodology involved a text-mining analysis of 526 English-language research articles on gender equality and sport development published from 2000 to 2021. The findings revealed a trajectory in the literature from an acritical stage towards more nuanced activation and liberation stages, varying across sociopolitical contexts. Key themes included the role of cultural norms, the impact of policy frameworks, and the emergence of intersectional approaches. The analysis highlighted a shift from focusing on participation rates to addressing systemic barriers and power dynamics within SFD contexts. While recent literature has developed more sophisticated analytical categories for examining gender equality in sport, there remains a gap in research exploring the role of sociopolitical agents in driving change. The study’s semantic configurations align closely with international sports frameworks, suggesting a strong influence of global policy on local SFD initiatives. This research provides a comprehensive, data-driven overview of how gender equality discourses in SFD have evolved over two decades. It underscores the importance of considering sociopolitical contexts in designing and implementing SFD programs to promote gender equality.